Uncertainty and sustainability in the management of semi-arid rangelands - Martin Quaas; Stefan Baumgärtner; Christian Becker; Karin Frank; Birgit Müller (University of Heidelberg, Department of Economics, 2004)
We analyze a dynamic and stochastic ecological-economic model of grazing management in semi-arid range lands. The non-equilibrium ecosystem is driven by stochastic precipitation. A risk averse farmer chooses a grazing management strategy under uncertainty such as to maximize expected utility from farming income. Grazing management strategies are rules about which share of the range land is given rest depending on the actual rainfall in that year. In a first step we determine the farmer's short-term optimal grazing management strategy. We show that a risk-averse farmer chooses a strategy such as to obtain insurance from the ecosystem: the optimal strategy reduces income variability, but yields less mean income than possible. In a second step we analyze the long-run ecological and economic impact of different strategies. We conclude that the more risk-averse a farmer is, the more conservative and sustainable is his short-term optimal grazing management strategy, even if he has no specific preference for the distant future.
Keywords: Q57; Q12; Q24; 330; Ecological-economic model; semi-arid range land; grazing management; risk aversion; uncertainty; sustainability; Weidewirtschaft; Risikoaversion; Nachhaltige Entwicklung; Umweltökonomik; Theorie; Entscheidung unter Unsicherheit